ASSESSMENT OF BEHAVIORAL PROBLEM AMONG SCHOOL CHILDREN AND HEALTH SEEKING BEHAVIOR OF PARENT IN SELECTED URBAN COMMUNITY, WEST BENGAL - Maiti, Sudipa; Ghosh, Prity (International Journal of Research -GRANTHAALAYAH, 2023)
Introduction: Behavioral problem are the reactions to emotional disturbance or environmental maladjustments. Behavioral problems in school aged children can cause significant difficulties in children’s healthy development. Aim: To find out the behavioral problem of school children and health seeking behavior of parents in urban community in Kolkata. Methods: A descriptive study was conducted to detect the behavioral problem of school children, health seeking behavior of parents, relationship of behavioral problem of school children and health seeking behavior of parents, association behavioral problem and health seeking behavior with selected demographic variables. A total of 150 participants were selected through Cluster sampling technique. Data were collected through Semi-structured Interview Schedule, Strength and Difficulties Questionnaire by Robert Goodman and Structured Interview Schedule to assess socio- demographic information, behavioral problems and Health seeking behavior of participants respectively. Result: Results revealed that 98 (65.33%) children belongs to normal category followed by abnormal category 30(20%) and borderline category 22(14.66%): area wise children’s behavioral problems mean% score of pro-social scale was (83.47%) followed by hyperactivity scale (73.47%), emotional problem (45.33%), conduct problem (37.47%) and peer problem (34%). Most of the mothers 28 (93.33%) had perceived behavioral problem of their child, 15 (50%) had taken action to relief the problem, 15 (50%) had seek advice from government hospital, only 3(10%) received treatment from Ojha, Quack practitioner, 27 (90%) perceived wrong decision cause delay or no health seeking. There was a positive correlation (0.222) between behavioral problem among school children and health seeking behavior of their parents. Age of mother and No. of siblings were significantly associated with behavioral problems; education of mother has been associated with health seeking behavior of mother having children with behavioral problem. Conclusion: Mental health of a child is of basic importance to gain the ability to live harmoniously in the changing environment. The community which neglects its children retards its future progresses. Children are dependent on their parents for their health and wellbeing. This study results focused that immediate need for regular assessment of children for early identification of behavioral problem.